The Politics of Un-recognition : Bedouin Villages in the Israeli Negev - Nevo, Issac (Yanni) (Hagar: Studies in Society and Culture, 2003)
In this paper I take a critical look into the policy of withholding official acknowledgement regarding the existence of Bedouin villages (as well as claims to land ownership) in the Israeli Negev. I argue that such policies are not merely discriminatory on an ethno-religious basis; that is to say, the very basis that defines Israel as a State; but that withholding such recognition from existing villages and communities is a particular, and distinctively pernicious, form of such ethnic and cultural discrimination, with its own attendant harms and social costs. In particular, the form of discrimination that is involved, and the harm that it brings about, can be accounted for in terms of the ideals of recognition and identity as universal human needs, and of the de-humanizing effects of a policy whose aim it is to outlaw a whole collective form of existence.